Turbulent heat transfer as a control of platelet ice growth in supercooled under-ice ocean boundary layers - McPhee, Miles G.; Stevens, Craig L.; Smith, Inga J.; Robinson, Natalie J. (Ocean Science, 2016)
Late winter measurements of turbulent quantities in tidally modulated flow under land-fast sea ice near the Erebus Glacier Tongue, McMurdo Sound, Antarctica, identified processes that influence growth at the interface of an ice surface in contact with supercooled seawater. The data show that turbulent heat exchange at the ocean–ice boundary is characterized by the product of friction velocity and (negative) water temperature departure from freezing, analogous to similar results for moderate melting rates in seawater above freezing. Platelet ice growth appears to increase the hydraulic roughness (drag) of fast ice compared with undeformed fast ice without platelets. Platelet growth in supercooled water under thick ice appears to be rate-limited by turbulent heat transfer and that this is a significant factor to be considered in mass transfer at the underside of ice shelves and sea ice in the vicinity of ice shelves.